IRAK4 inhibition: an effective strategy for immunomodulating peri-implant osseointegration via reciprocally-shifted polarization in the monocyte-macrophage lineage cells - Juan Zhao; Jia Li; Antian Xu; Yangbo Xu; Fuming He; Yingjie Mao (BMC, 2023)
Abstract Background The biomaterial integration depends on its interaction with the host immune system. Monocyte-macrophage lineage cells are immediately recruited to the implant site, polarized into different phenotypes, and fused into multinucleated cells, thus playing roles in tissue regeneration. IL-1R-associated kinase 4 (IRAK4) inhibition was reported to antagonize inflammatory osteolysis and regulate osteoclasts and foreign body giant cells (FBGCs), which may be a potential target in implant osseointegration. Methods In in-vitro experiments, we established simulated physiological and inflammatory circumstances in which bone-marrow-derived macrophages were cultured on sand-blasted and acid-etched (SLA) titanium surfaces to evaluate the induced macrophage polarization, multinucleated cells formation, and biological behaviors in the presence or absence of IRAK4i. Then, bone marrow stromal stem cells (BMSCs) were cultured in the conditioned media collected from the aforementioned induced osteoclasts or FBGCs cultures to clarify the indirect coupling effect of multinucleated cells on BMSCs. We further established a rat implantation model, which integrates IRAK4i treatment with implant placement, to verify the positive effect of IRAK4 inhibition on the macrophage polarization, osteoclast differentiation, and ultimately the early peri-implant osseointegration in vivo. Results Under inflammatory conditions, by transforming the monocyte-macrophage lineage cells from M1 to M2, IRAK4i treatment could down-regulate the formation and activity of osteoclast and relieve the inhibition of FBGC generation, thus promoting osteogenic differentiation in BMSCs and improve the osseointegration. Conclusion This study may improve our understanding of the function of multinucleated cells and offer IRAK4i as a therapeutic strategy to improve early implant osseointegration and help to eliminate the initial implant failure.